1987
DOI: 10.1590/s0074-02761987000800067
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni: structural damage after treatment with oxamniquine

Abstract: The effects of a single dose (100 mg/kg-body weight of mouse) of oxamniquine on the worm's tegument and paranchyma in relation to the process of immunological granulomatous reaction of the host's liver are described under light and electron microscopy (EM). The lesions caused by the drug are sequentially and simultaneously described in form of swelling, surface bulble and disruption with erosions. Ulceration in the tubercules with loss of spines is often more extensive and severe in male worms and concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The surface topography of adult schistosomes has been exhaustively visualized in a number of scanning electron microscope (SEM) studies (Miller et al 1972, Hockley 1973, Kuntz et al 1976, Sakamoto & Ishii 1977, McLaren 1980, which also showed tegumental alterations after schistosomicides treatment (Kohn et al 1982, Magalhães Filho 1987 or after incubation in various media (Kalapothakis et al 1988). Recently, we have demonstrated that the far anterior region of the gynaecophoric canal is spiness, the right side of the gynaecophoric canal presents a greater amount of tubercles compared to the other in which the spines prevailed.…”
mentioning
confidence: 99%
“…The surface topography of adult schistosomes has been exhaustively visualized in a number of scanning electron microscope (SEM) studies (Miller et al 1972, Hockley 1973, Kuntz et al 1976, Sakamoto & Ishii 1977, McLaren 1980, which also showed tegumental alterations after schistosomicides treatment (Kohn et al 1982, Magalhães Filho 1987 or after incubation in various media (Kalapothakis et al 1988). Recently, we have demonstrated that the far anterior region of the gynaecophoric canal is spiness, the right side of the gynaecophoric canal presents a greater amount of tubercles compared to the other in which the spines prevailed.…”
mentioning
confidence: 99%
“…This phenomenon was previously observed when schistosomes were exposed to oxamniquine 40 and ginger extracts. 43 However, a unique phenomenon which was noticed in this study was the fusion of the edges of the gynaecophoric canal at some sites. This might be behind the uncoupling of worms which was observed in this study and was also caused by crude pomegranate extracts in another study.…”
Section: Discussionmentioning
confidence: 59%
“…The alterations of the schistosomal tegument by various natural and synthetic antischistosomal drugs have been previously reported. Examples of these natural and synthetic drugs are artemether, 35 astiban, 36 amoscanate, 37 hycanthone, 38 niridazole, 39 aspidine and flavaspidic acid purified from the rhizomes of Dryopteris species, 40 artesunate, 41 mirazid purified from myrrh oleoresin 42 and ginger aqueous extract, 43 oxamniquine 44 and praziquantel. 10 In this study, ellagitannins led also to the release of tegumental blebs.…”
Section: Discussionmentioning
confidence: 99%
“…Using SEM, Kohn et al [35] noticed that the drug was producing changes in the structure of the worm on tegumental, muscular and parenchymal levels, causing bubble-like lesions. Magalhães-Filho et al [36] also noticed vacuolization, destruction of tubercles in male worms, and surface erosion. Recently, praziquantel has been subjected to further studies because it still is the most used drug in the treatment of all types of schistosomiasis.…”
Section: The Analysis Evolution Of the Tegument Of S Mansoni: From Omentioning
confidence: 92%